17.0k views
3 votes
Need help with this question!

Need help with this question!-example-1
User TonyK
by
5.1k points

2 Answers

2 votes

Explanation:

a=(x + 3)

b=2x

c=(2x + 2.4)

(x + 3)^2 + 2x^2 = (2x + 2.4)^2

=3x^2 + 6x + 9 = 4x^2 + 9.6x +5.76

= -x^2 - 3.6x + 3.24 = 0

now we have a quadratic equation so

a= -x

b= -3.6

c= 3.24


x=
-(3.6 + √(25.92) )/(2) ,
x=(√(25.92) -3.6)/(2)

User Raj Saraogi
by
4.6k points
5 votes
not sure:((((((( sorrryyyy
User DaJackal
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.